Data Quality in Health Care: Main Concepts and Assessment Methodologies - Mashoufi, Mehrnaz; Ayatollahi, Haleh; Khorasani-Zavareh, Davoud; Talebi Azad Boni, Tahere (Methods of Information in Medicine, 2023)
Introduction In the health care environment, a huge volume of data is produced on a daily basis. However, the processes of collecting, storing, sharing, analyzing, and reporting health data usually face with numerous challenges that lead to producing incomplete, inaccurate, and untimely data. As a result, data quality issues have received more attention than before.Objective The purpose of this article is to provide an insight into the data quality definitions, dimensions, and assessment methodologies.Methods In this article, a scoping literature review approach was used to describe and summarize the main concepts related to data quality and data quality assessment methodologies. Search terms were selected to find the relevant articles published between January 1, 2012 and September 31, 2022. The retrieved articles were then reviewed and the results were reported narratively.Results In total, 23 papers were included in the study. According to the results, data quality dimensions were various and different methodologies were used to assess them. Most studies used quantitative methods to measure data quality dimensions either in paper-based or computer-based medical records. Only two studies investigated respondents' opinions about data quality.Conclusion In health care, high-quality data not only are important for patient care, but also are vital for improving quality of health care services and better decision making. Therefore, using technical and nontechnical solutions as well as constant assessment and supervision is suggested to improve data quality.
Keywords: health; data quality; documentation; assessment